2020
DOI: 10.1109/tmc.2019.2910256
|View full text |Cite
|
Sign up to set email alerts
|

Duopoly Competition for Mobile Data Plans with Time Flexibility

Abstract: The growing competition drives the mobile network operators (MNOs) to explore adding time flexibility to the traditional data plan, which consists of a monthly subscription fee, a data cap, and a per-unit fee for exceeding the data cap. The rollover data plan, which allows the unused data of the previous month to be used in the current month, provides the subscribers with the time flexibility. In this paper, we formulate two MNOs' market competition as a three-stage game, where the MNOs decide their data mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…For example, the rollover data plan offered by AT&T requires that the rollover data from the previous month should be consumed after the current monthly data cap [6], while China Mobile requires the other way around [7]. In our previous work [8], [9], we analyzed the MNO's optimal data plan with time flexibility under the single-cap scheme (without price discrimination) and found that the time flexibility can increase both the MNO's profit and users' payoff, hence improve the social welfare. This motivates us to ask the second key question in this paper.…”
Section: Question 1 How Should the Mno Optimize The Multi-cap Data Pmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the rollover data plan offered by AT&T requires that the rollover data from the previous month should be consumed after the current monthly data cap [6], while China Mobile requires the other way around [7]. In our previous work [8], [9], we analyzed the MNO's optimal data plan with time flexibility under the single-cap scheme (without price discrimination) and found that the time flexibility can increase both the MNO's profit and users' payoff, hence improve the social welfare. This motivates us to ask the second key question in this paper.…”
Section: Question 1 How Should the Mno Optimize The Multi-cap Data Pmentioning
confidence: 99%
“…Section 3 introduces the system model. Section 4 analyzes the contract feasibility [10]- [13] No No [8] [9][14]- [16] Yes No [17] No Yes (but limited) This Paper Yes Yes and Section 5 studies the contract optimality. In Section 6, we present the numerical results.…”
Section: Solutions and Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary data trading is not convenient for operation, since the consumer has to buy or sell every time when he is running out of data or has data left unused. The papers [16], [17], [18], [19], [20] are the pioneer works that study the rollover data plan. Zheng et al in [16] evaluated the benefits of rollover data for both SPs and users as well as identify the types of users who would upgrade to rollover data plans.…”
Section: Related Literature On Data Pricing Schemesmentioning
confidence: 99%